Hip Involvement in Juvenile Idiopathic Arthritis: A Roadmap From Arthritis to Total Hip Arthroplasty or How Can We Prevent Hip Damage? - Sorokina, Lubov S.; Avrusin, Ilia S.; Raupov, Rinat K.; Lubimova, Natalia A.; Khrypov, Sergey V.; Kostik, Mikhail M. (Frontiers in Pediatrics, 2021)
Objectives: To describe the clinical characteristics of hip involvement in juvenile idiopathic arthritis (JIA) from arthritis to hip osteoarthritis (HOA) and total hip arthroplasty (THA). Study Design: Seven hundred fifty-three patients aged 2–17 years with JIA were included in the study. The comparison analysis was performed between the following subgroups: (i) JIA without hip involvement (n = 600; 79.7%) vs. JIA with hip involvement without HOA (n = 105; 13.9%), (ii) JIA with hip involvement with HOA, but without THA (n = 32; 4.3%) and JIA with hip involvement with HOA and with THA (n = 16; 2.1%). Clinical, laboratory characteristics and treatment regimens compared. Results: Hip involvement was present in 20.3% of patients. HOA was present in 6.4% (12*1,000 patient-years) of the entire JIA group and 31.4% of patients with hip involvement. Sixteen patients (2.1%; 4.0*1,000 patient-years) required THA. The following factors were associated with HOA: sJIA (OR = 3.6, p = 0.008; HR = 3.0, p = 0.002), delayed remission (OR = 4.2, p = 0.004; HR = 1.4, p = 0.538), delay in biologic therapy initiation (OR = 7.5, p = 0.00001; HR = 6.7, p = 0.002), alkaline phosphatase <165 Uł (OR = 4.1, p = 0.0003; HR = 5.2, p = 0.000004), treatment with corticosteroids (CS) (OR = 2.6, p = 0.008; HR = 1.2, p = 0.670), cumulative corticosteroids >2,700 mg (OR = 4.3, p = 0.032; HR = 1.4, p = 0.527). The following factors were associated with THA: delay in biologic treatment initiation (OR = 1.04, p = 0.0001; HR = 9.1, p = 0.034), delayed hip involvement (OR = 5.2, p = 0.002; HR = 3.0, p = 0.044), and methylprednisolone pulse therapy (OR = 10.8, p = 0.0000001; HR = 5.6, p = 0.002). Conclusion: Both sJIA and systemic CS, impaired calcium-phosphorus metabolism, and delayed hip arthritis are associated with HOA development in JIA. HOA is considered to be a severe adverse event of CS treatment, especially delayed hip involvement.